Local transversal aortic strain is impaired in ascending aorta dilatation. Issue 7 (July 2021) - Cesareo, Marco; Sabia, Luca; Leone, Dario; Avenatti, Eleonora; Astarita, Anna; Mingrone, Giulia; Airale, Lorenzo; Veglio, Franco; Vallelonga, Fabrizio; Milan, Alberto
Abstract : Background: Ascending aorta dilatation is found in 13% of hypertensive patients. Little is known about elastic properties of ascending aorta in such patients. Echo-based transverse aortic strain analysis can describe mechanical properties of ascending aorta but has never been applied to patients with ascending aorta dilatation. Aim: To assess mechanical properties of ascending aorta by transverse aortic strain analysis (as β2 - stiffness index ) in hypertensive patients with ascending aorta dilatation and association between mechanical properties of ascending aorta and cardiovascular damage. Methods: A total of 100 hypertensive outpatients underwent transthoracic echocardiography and assessment of pulse wave velocity (PWV). Strain analysis of ascending aorta was performed with echocardiographic speckle-tracking software. Patients were divided in three groups based on ascending aorta diameter: less than 40, 40–45, and at least 45 mm. Results: Beta-SI increased exponentially with ascending aorta dimensions ( P < 0.001). Patients with ascending aorta dilatation had Beta-SI significantly higher than those with normal ascending aorta diameter. A greater proportion of patient with impaired (i.e., elevated) Beta-SI was present in groups with larger ascending aorta (18.2 vs. 48.4 vs. 80%, respectively, P < 0.05). On multivariate logistic regression only impaired Beta-SI predicted ascending aorta dilatation ( P < 0.001). Beta-SI was related to cardiovascular damage in terms of left ventricular (LV) mass (LV mass indexed to BSA, P = 0.030) and PWV ( P = 0.028). Patients with high Beta-SI had greater LV mass indexed to BSA (117 ± 47 vs. 94 ± 24 g/m 2 ; P = 0.010) and PWV (10.20 ± 2.99 vs. 8.63 ± 1.88 m/s; P = 0.013). Conclusion: Ascending aorta dilatation is associated with increased local aortic stiffness in hypertensive patients. Strain analysis adds functional information to the mere morphological evaluation of aortic diameter and could be a useful tool to better define cardiovascular risk in this population. Abstract : Supplemental Digital Content is available in the text